Government Funding of University-Industry Collaboration: Exploring the Impact of Targeted Funding on University Patent Activity - Annita Nugent; Ho Fai Chan; Uwe Dulleck (Center for Economic Studies and ifo Institute (CESifo), 2019)
Government investment in university research results in greater output and impact. To better capture economic benefits stemming from university research, governments have developed funding programs specifically targeting university-industry collaboration. However, little is known about the success of university-industry targeted (U-I targeted) grants. In this study we evaluate the effect of one such scheme, the Australian Research Council (ARC) Linkage Project scheme, by comparing it to its non-targeted sister scheme, the ARC Discovery Project scheme. Having in common selection criteria, grant assessors, awardees, magnitude of funding and duration, the schemes differ in the requirement for an industry partner. We measure capture of economic benefit by patent applications filed and granted. Interrogating the effect of targeted funding at a university level we find award of U-I targeted grants coincides with increased patent activity compared to non-targeted grants. Exploring the dynamics of the relationship, we observe the effect of U-I targeted grants on patent activity is short lived at an inventor level. Further, the propensity for patent activity is influenced by the ratio of U-I targeted to non-targeted grants held at a university level, but not at an inventor level.
Keywords: O34; O38; 330; research funding; patent; university-industry collaboration; grants